Impact of nutrition education on nutrition knowledge, attitudes, and practices among adolescent girls in Bogor, Indonesia - Widya Azhari Salma; Tande Ribka; Azmi Zaqia Zulfani Zahida; Ramadani Elvy; Rahmah Dinitya Khalishah; Fauziah Toruntju Ainun; Kustiyah Lilik; Anna Marliyati Sri; Hardinsyah; Cahya Alam Duta (BIO Web of Conferences)
Nutrition education is a potentially effective intervention for improving adolescent’s nutritional status. This study aims to analyze the effects of nutrition education on the scores of nutrition knowledge, attitude, and practice of adolescent girls at SMAN 1 Dramaga, Bogor, Indonesia in 2024. This study employed a quasi-experimental research with purposive sampling on 41 adolescent girls. The intervention consisted of seven one- hour education sessions. The educational materials and methods were different in each meeting. A paired sample t-test indicates a significant difference in both knowledge and practice scores before and after the education intervention (p < 0.001), although no significant difference was found in attitude scores (p=0.513). These findings suggest that the existing nutrition education model could improve the nutrition knowledge and practices among adolescent girls.